STRATEGY FOR ACHIEVING HIGH RESULTS IN THE PROCESS OF TEACHING MATHEMATICS IN SECONDARY SCHOOLS - Pirimqulova, Nafisa (SAMBHRAM XABARNOMASI, 2024)
Annotation: This article contains a solution to problems aimed at improving the relationship between teachers and students in secondary schools. In addition, what is High Impact Teaching Strategies and their application methods are presented in the article. These High Impact Teaching Strategies (HITS) have been brought together here to support the thousands of increasingly collaborative and evidence-based conversations taking place between teachers in schools each day. These strategies provide teachers and teams with opportunities to observe, reflect on and improve a range of fundamental classroom practices.